2018
DOI: 10.1038/s41375-018-0153-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma clonal evolution in homogeneously treated patients

Abstract: Clonal evolution drives tumor progression, chemoresistance and relapse in cancer. Little is known about clonal selection induced by therapeutic pressure in multiple myeloma. To address this issue, we performed large targeted sequencing of bone marrow plasma cells in 43 multiple myeloma patients at diagnosis and at relapse from exactly the same intensive treatment. The most frequently mutated genes at diagnosis were KRAS (35%), NRAS (28%), DIS3 (16%), BRAF, and LRP1B (12% each). At relapse, the mutational burde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
98
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 39 publications
14
98
0
1
Order By: Relevance
“…The potential impact of specific therapeutic agents, including novel agents, on the risk of developing HEMM remains unclear. Current evidence support that therapy itself may contribute to sub‐clonal selection . A complex treatment history (defined in the presence of a higher number of therapies [>2 lines] administered over ≥6 months) has been recently reported to be associated with an increased risk for extramedullary relapse .…”
Section: Discussionmentioning
confidence: 79%
“…The potential impact of specific therapeutic agents, including novel agents, on the risk of developing HEMM remains unclear. Current evidence support that therapy itself may contribute to sub‐clonal selection . A complex treatment history (defined in the presence of a higher number of therapies [>2 lines] administered over ≥6 months) has been recently reported to be associated with an increased risk for extramedullary relapse .…”
Section: Discussionmentioning
confidence: 79%
“…Following examples from other cancers, several efforts have been put in place to use genomics to explain chemoresistance in relapsed disease. Indeed, serial analysis of pre-treatment and relapsed MM samples again showed a tendency toward evolution, where a change in subclonal structure was often observed together with an enrichment of high-risk features (17,34,35). Confirming the higher prevalence of high-risk lesions in more aggressive stages, NGS analysis of primary plasma cell leukemia, a rare extramedullary presentation of a clonal plasma cell dyscrasia, showed increased prevalence of TP53 mutations and del(17p) (36).…”
Section: Molecular Pathogenesis Of Multiple Myeloma and Related Monocmentioning
confidence: 86%
“…For this reason, the choice of the experiment is greatly influenced by the research-diagnostic question, but also by the instrument/technology available and the sample load in each laboratory. Currently, for clinical purposes a targeted panel able to detect mutations, copy number alterations and all the known IGH/IGK/IGL rearrangements represents the most cost-effective solution for risk stratification in MM (21,35,58,(62)(63)(64). However, this approach is intrinsically limited for research in that it requires prior knowledge of what to look for, and hence it might miss unknown -but relevanttranslocations or gene mutations.…”
Section: Next Generation Sequencing the Technique Of Next-generation mentioning
confidence: 99%
“…Interestingly, very few nonrecurring mutations or aneuploidies were found in proteasome subunit genes in our cohort, confirming their rarity. 16,55 We assessed high-risk genetic 3 ), double-hit events, 11 apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like (APOBEC) signature contribution, 13 TP53 mutations, 9 and CRBN pathway mutations 15 and found that at least 1 such event was present in 65% of patients ( Figure 2D).…”
Section: Genomic Makeup Of Treatment-resistant Samplesmentioning
confidence: 99%